‘Berlin Sees Bizarre Russian Art Show’: The Press Coverage of the Erste Russische Kunstausstellung (1922) and the Perception of Russia’s Modernist Art - Miriam Leimer (The February Journal, 2023)
The Erste Russische Kunstausstellung (First Russian Art Exhibition) that took place in Berlin in 1922 was an important event for the development of modernism. International artists and patrons visited the show at the Galerie van Diemen that combined paintings from late Tsardom and the pre-revolutionary avant-garde with the recent artistic production of Russia’s non-objective art movements. While the role of the Van Diemen show for the progressive international art scene in the early 1920s has long been acknowledged, little is known about the perception of this ‘Russian’ labeled modernism among the general public that encountered now-iconic art works by Vladimir Tatlin, Aleksandr Rodchenko, and Kazimir Malevich. By analyzing the coverage of the exhibition in newspapers and art journals, mostly from the Weimar Republic, this article highlights the Western interpretation of the newly discovered suprematism and constructivism as well as their radical new aesthetics.